ANALISIS E-SERVICE QUALITY TERHADAP E-LOYALTY: STUDI PENGGUNA GOPAY PADA GENERASI X, Y, DAN Z - Wati, Ina Kartika; Mumdin, Ali; Soma, AM (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2024)
Background: The use of Electronic Payment Systems has permeated daily life, influencing the financial habits of various generations. In this context, GoPay, as a Digital Payment System provider, needs to understand the impact of Electronic Service Quality (E-SerQual) on the financial habits and consumer loyalty of Generation X, Millennials, and Generation Z. Research Objective: The study aims to investigate how E-SerQual on GoPay affects the level of user loyalty across three different generations. Factors such as system availability, fulfillment, responsiveness, and compensation will be evaluated to understand their impact on users' decisions to continue using the GoPay service. Method: The research employs a quantitative confirmatory method using the Smart PLS application. One hundred fifty respondents from three generations participated, with multi-group analysis used to compare the results among Generation X, Millennials, and Generation Z. Findings: The research results indicate a positive and significant relationship between E-SerQual and E-Loyalty in all generations. Generation Z shows the most robust impact, followed by Millennials, and then Generation X. Results and Recommendations: It was found that understanding the different preferences and responses of each generation is crucial for developing more effective marketing strategies. Recommendations include enhancing the electronic service experience to improve consumer loyalty across all generations.